Socioeconomic disadvantage and the risk of advanced chronic kidney disease: results from a cohort study with 1.4 million participants - Weldegiorgis, M; Smith, M; Herrington, WG; Bankhead, C; Woodward, M (Oxford University Press, 2019)
Background Several studies have investigated the effect of socioeconomic deprivation on cardiovascular disease (CVD) and diabetes; less is known about its effect on chronic kidney disease (CKD). We aimed to measure the association between deprivation, CKD Stages 4–5 and end-stage renal disease (ESRD) in a general population sample.